Good’s Syndrome: Time to Move on From Reviewing the Past - Kabir, Aunonna; Alizadehfar, Reza; Tsoukas, Christos M. (Frontiers in Immunology, 2022)
For seven decades, the pathophysiology of Good’s syndrome has remained a mystery, with few attempts to solve it. Initially described as an association between hypogammaglobinemia and thymoma, there has long been a controversy whether this is a unique disease or a subgroup of Common Variable Immune Deficiency (CVID). In recent years, distinguishing aspects of both syndromes have come to light that may reflect fundamental differences in their underlying pathophysiology. In Good’s syndrome there is a paucity or absence of peripheral B cells, while in CVID, one distinguishing feature is low memory B cells. Similarly, differences in T cell dysregulation and manifestations of cytopenias may further distinguish Good’s syndrome from other Inborn Errors of Immunity (IEI). Knowledge of the clinical phenotype of this very rare adult immune deficiency stems from individual case reports, and retrospective and cross-sectional data on a few cohorts on a limited number of patients. Understanding the pathophysiology of this syndrome is hampered by incomplete and inconsistent reporting of hematologic and immune parameters, and lack of adequately powered longitudinal and experimental studies. In this mini-review we discuss the current knowledge, identify research gaps and propose that we move forward in a coordinated shift from incidence reporting to robust investigative studies in order to resolve controversies and identify mechanisms of disease.